Low p14ARF expression in neuroblastoma cells is associated with repressed histone mark status, and enforced expression induces growth arrest and apoptosis - Dreidax, Daniel; Gogolin, Sina; Schroeder, Christina; Muth, Daniel; Brückner, Lena Marie; Hess, Elisa Maria; Zapatka, Marc; Theißen, Jessica; Fischer, Matthias; Ehemann, Volker; Schwab, Manfred; Savelyeva, Larissa; et al. (Human molecular genetics, 2013)
The TP53 tumor suppressor pathway is abrogated by TP53 mutations in the majority of human cancers. Increased levels of wild-type TP53 in aggressive neuroblastomas appear paradox but are tolerated by tumor cells due to co-activation of the TP53 ubiquitin ligase, MDM2. The role of the MDM2 antagonist, p14ARF, in controlling the TP53-MDM2 balance in neuroblastoma is unresolved. In the present study, we show that conditional p14ARF expression substantially suppresses viability, clonogenicity and anchorage-independent growth in p14ARF-deficient or MYCN-amplified neuroblastoma cell lines. Furthermore, ectopic 14ARF expression induced accumulation of cells in the G1 phase and apoptosis, which was paralleled by accumulation of TP53 and its targets. Comparative genomic hybridization analysis of 193 primary neuroblastomas detected one homozygous deletion of CDKN2A (encoding both p14ARF and p16INK4A) and heterozygous loss of CDKN2A in 22% of tumors. Co-expression analysis of p14ARF and its transactivator, E2F1, in a set of 68 primary tumors revealed only a weak correlation, suggesting that further regulatory mechanisms govern p14ARF expression in neuroblastomas. Intriguingly, analyses utilizing chromatin immunoprecipitation revealed different histone mark-defined epigenetic activity states of p14ARF in neuroblastoma cell lines that correlated with endogenous p14ARF expression but not with episomal p14ARF promoter reporter activity, indicating that the native chromatin context serves to epigenetically repress p14ARF in neuroblastoma cells. Collectively, the data pinpoint p14ARF as a critical factor for efficient TP53 response in neuroblastoma cells and assign p14ARF as a neuroblastoma suppressor candidate that is impaired by genomic loss and epigenetic repression.
Gesehen am 04.01.2021